Advanced AlN/SiO2/AlN multilayer coatings for protecting gold-like decorative surfaces: Improved hardness and color stability - Raengroeng, Sitanan; Theekhasuk, Nattharika; Sakulkalavek, Aparporn; Sakdanuphab, Rachsak; Somdock, Nuttakrit (My University, 2025)
This study explores the development of multilayer AlN/SiO2/AlN thin film coatings to enhance tarnish resistance, surface hardness, and color stability of gold-coated silver substrates for decorative use. Gold films were deposited via electroplating, followed by multilayer coatings using reactive magnetron sputtering. The SiO2 thickness was systematically varied while maintaining fixed AlN layers. Optical evaluations using CIE Lab parameters confirmed that the specimen with a 110-min SiO2 layer exhibited acceptable color difference (ΔE < 5). X-ray photoelectron spectroscopy (XPS) revealed stable Al–N and Si–O bonds with minimal oxidation. Nanoindentation tests showed a significant hardness increase, reaching 7.02 ± 0.62 GPa. After 240 days of ambient exposure, multilayer-coated samples showed no visible discoloration or sulfur-induced degradation, unlike uncoated and electrochemically coated samples. These results confirm that AlN/SiO2/AlN multilayers effectively improve the durability and aesthetic stability of gold-like surfaces, offering a promising solution for long-term decorative applications.
Keywords: Color changes and scratches; Gold-like jewelry; Multi-layer